English - Indonesian Translation Strategies Made By Vocational Students - Singgih Widodo Limantoro; Yerly Arnold Datu (Fakultas Bahasa dan Budaya Asing (FBBA), Universitas Muhammadiyah Semarang, 2021)
Translation for the vocational students of the Business English study program could be considered as the fifth language skill that they need to learn in multilingual digital era. Therefore, they have to be able to translate and interpret from English text to the Indonesian text and vice versa in some business applications, such as tourism/ hospitality industry, export import, and customer service. In this paper, the writers used qualitative descriptive research on the case study taken from the Translation classroom. To achieve the purposes of the study, the writer would like to compare the results of the respondents' target translation between translating the source text without and with translation strategies in facilitating their academic learning process. In this survey, the writer found out that most of the participations used Google Translate and translation strategies, such as structural and semantic translation strategies to help them facilitate their translating to produce qualified translation results. Based on the results, the translation strategies were useful for novice translators. The other findings were what factors that influenced their errors in English- Indonesian translation and what translation strategies. The writers also shared some important educational implications of this research